Prevalence of undiagnosed hypertension amongst dental patients in the University College Hospital, Ibadan Oyo State, Nigeria - Opeodu, Olanrewaju; Adeyemi, Bukola F. (Journal of Stomatology, 2017)
Introduction. Hypertension is one of the medical conditions that are of great importance in the management of dental patients. It may present as an emergency during dental treatment or necessitate a change in patient’s management. Aim of the study. To determine the prevalence of undiagnosed hypertension and the level of control in diagnosed hypertensive patients presenting at a dental outpatient clinic in Nigeria. Material and methods. A crosssectional survey of patients presenting at the Dental Outpatient Clinic of a Nigerian tertiary hospital was undertaken. Consenting patients above 15 years of age had their blood pressure assessed with the aid of a digital sphygmomanometer. The relationship between blood pressure and body mass index, family history of hypertension as well as socioeconomic status were assessed. Statistical significance was set at p < 0.05. Results. A total of 552 subjects were recruited, with 107 (19.4%) previously on antihypertensive drugs but only 14 (13.0%) on an antihypertensive had a normal blood pressure. Forty-one (9.2%) subjects were hypertensive but were not aware of it. There was a statistically significant relationship between positive family history of high blood pressure and high diastolic blood pressure. There was also a statistically significant relationship between blood pressure and age (p< 0.05). Conclusion. The study demonstrated that hypertensive patients constitute an important proportion of dental patients. Thus, the dental profession has a unique role in the early detection of hypertension. Also patients’ opinion of their blood pressure may be insufficient for optimal dental management.